Nutrient Use Efficiency of Southern South America Proteaceae Species. Are there General Patterns in the Proteaceae Family? - Delgado, Mabel; Valle, Susana; Reyes-Díaz, Marjorie; Barra, Patricio J.; Zúñiga-Feest, Alejandra (Frontiers in Plant Science, 2018)
Plants from the Proteaceae family can thrive in old, impoverished soil with extremely low phosphorus (P) content, such as those typically found in South Western Australia (SWA) and South Africa. The South Western (SW) Australian Proteaceae species have developed strategies to deal with P scarcity, such as the high capacity to re-mobilize P from senescent to young leaves and the efficient use of P for carbon fixation. In Southern South America, six Proteaceae species grow in younger soils than those of SWA, with a wide variety of climatic and edaphic conditions. However, strategies in the nutrient use efficiency of Southern South (SS) American Proteaceae species growing in their natural ecosystems remain widely unknown. The aim of this study was to evaluate nutrient resorption efficiency and the photosynthetic nutrients use efficiency by SS American Proteaceae species, naturally growing in different sites along a very extensive latitudinal gradient. Mature and senescent leaves of the six SS American Proteaceae species (Embothrium coccineum, Gevuina avellana, Orites myrtoidea Lomatia hirsuta, L. ferruginea, and L. dentata), as well as, soil samples were collected in nine sites from southern Chile and were subjected to chemical analyses. Nutrient resorption (P and nitrogen) efficiency in leaves was estimated in all species inhabiting the nine sites evaluated, whereas, the photosynthetic P use efficiency (PPUE) and photosynthetic nitrogen (N) use efficiency (PNUE) per leaf unit were determined in two sites with contrasting nutrient availability. Our study exhibit for the first time a data set related to nutrient use efficiency in the leaves of the six SS American Proteaceae, revealing that for all species and sites, P and N resorption efficiencies were on average 47.7 and 50.6%, respectively. No correlation was found between leaf nutrient (P and N) resorption efficiency and soil attributes. Further, different responses in PPUE and PNUE were found among species and, contrary to our expectations, a higher nutrient use efficiency in the nutrient poorest soil was not found. We conclude that SS American Proteaceae species did not show a general pattern in the nutrient use efficiency among them neither with others Proteaceae species reported in the literature.